Determination of the Impact of Mating on Stress Protein in Different Honey Bee Breeds - Kabakci, Dilek; Bozkurt, Aybike Sarıoğlu; Sonmez, Oner; Gunes, Nazmiye (My University, 2024)
The queen is the only individual with a colony of bees and the ability to reproduce. This study determined the level of stress proteins (Hsp70) in mated and virgin queens reared under the same conditions in colonies of honey bee breeds and ecotypes in Turkey. When the effects of mating were examined, it was found that the stress protein content of mated queens was significantly lower than that of non-mated queens (p<0.05). It was also found that Hsp70 stress protein levels were lower in Thrace, Yığılca and Gökçeada ecotypes, which are the sub- ecotypes of the Anatolian bee, compared to other ecotypes and races. As a result, it was found that the adaptive abilities of Trakya, Gökçeada and Yığılca ecotypes, which are the sub- ecotypes of the Anatolian bee found in our country, are better than those of other subspecies.
Keywords: Honey bee, Queen, Subspecies, Mating effect, Stress protein (Hsp70)